Effects of positive end-expiratory pressure on cardiac hemodynamic and autonomic balance in patients on invasive mechanical ventilation: a clinical trial (Research, Society and Development, 2021)
Objective: To evaluate the effect of increasing positive end-expiratory pressure (PEEP) on hemodynamics and cardiac autonomic balance in patients using invasive mechanical ventilation (IMV). Methodology: This is a non-probabilistic study, where patients are their own controls, in critically ill patients hospitalized after 24 hours, submitted to increasing levels of PEEP (8, 12 and 15 cmH2O) 15 min per increment. Results: Thirty patients were included in the study. No changes were found in hemodynamic variables and cardiac autonomic balance among patients who underwent increasing levels of PEEP (8, 12 and 15 cmH2O). Conclusion: In the present study, PEEP levels of 8, 12 and 15 cmH2O did not promote changes in hemodynamic responses and cardiac autonomic balance in patients on invasive mechanical ventilation.